Controlling and Experimental Validation of an Air Compressor System with Energy Efficient Novel Pressurized Air Cabin for Open-Cathode PEM Fuel Cell - Mert Ali Özel; Osman Sümer (Applied Sciences, 2025)
This study investigates a novel pressurized cabin system for open-cathode proton exchange membrane (PEM) fuel cells to enhance energy efficiency and performance. The urgency of this study lies in the increase in the uniformity index (UI) and the decrease in pressure loss, which are crucial parameters of the air supply system. It optimizes the cabin’s 3D geometry using the Taguchi method, achieving a 3.68% increase in UI and a 7.69% reduction in pressure drop. A 1D mathematical model developed for system control demonstrates the pressurized cabin’s superior efficiency compared to conventional air supply systems. Experimental results validate these findings, showing around an 8% reduction in energy consumption and a 9.4% improvement in power output. These results indicate that the novel cabin design offers substantial performance benefits, making it a valuable contribution to energy-efficient fuel cell technology.